Puerperal Sepsis and its Cause in Patan Hospital - Pradhan, B; Duwal, SS; Singh, A; Bhandary, S; RC, L; Shrestha, R (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study was done to find out morbidity related with puerperal pyrexia/sepsis and its risk factors. Methods: This was retrospective study conducted from January 2011 to December 2012 at Department of Obstetrics and Gynaecology, Patan Hospital, Kathmandu, Nepal. All women who delivered in this hospital within 42 days of delivery with puerperal pyrexia/sepsis diagnosed on clinical examination and relevant investigations were included in the study. Women with malaria, typhoid fever and ??other fever were excluded. The data was recorded in predesigned proforma and analyzed. Results: During this period, there were 122 cases of puerperal pyrexia. Puerperal pyrexia accounted for 6.28% of 1945 admissions. Most of the women were aged between 20-29 years, primiparous and booked cases with absent membranes. The causes of puerperal pyrexia in our study were urinary tract infection (47.5%), wound infection (20.5%), endometritis (19.7%) retained product of conception (8.2%), pyoperitoneum (2.5%) and septicemia (1.6%). Conclusions: Puerperal pyrexia/sepsis is one of the causes of preventable maternal morbidity and mortality though in our study it was not proved to be very high in number. Optimal aseptic measures during labour can prevent most of the cases.